The relationship between total quality management and corporate social responsibility among Yemeni pharmaceutical firms - Abdulwahid, Khalifah; Al-Nashmi, Murad Mohammed; Daud, Nur Aizati Athirah; Alqasemi, Fahd A. (Inderscience Publishers, 2024)
Globally, there is a scarcity of studies related to total quality management (TQM) in association with social responsibility in the context of the pharmaceutical industry. The study empirically evaluates the relationship between TQM and corporate social responsibility (CSR) in Yemeni pharmaceutical manufacturing firms through the effect of TQM critical success factors (CSFs). A survey questionnaire was design based on the most frequently cited TQM-CSF in literature. The hypotheses testing at P value ? 0.05 revealed a significant and positive correlation between TQM critical success factors (leadership commitment, continuous improvement, employees' involvements, and customer focus) and CSR, whereby the r-values were 0.470, 0.389, 0.498, and 0.589 respectively. The study found that critical success factors of TQM positively influence CSR practice. The study insight extends the current body of literature by empirically testing the applicability of TQM-CSR in broader aspects of future research.